{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

prelim2_fa09solutions

# prelim2_fa09solutions - Math 1910 Prelim 2 Solutions 1 a...

This preview shows pages 1–2. Sign up to view the full content.

Math 1910, Prelim 2 October 29, 2009 Solutions 1) a) Letting u = ln( x ) we have du = dx x , x = 1 u = 0, x = 2 u = ln(2). Thus Z 2 1 log 2 ( x ) x dx = 1 ln(2) Z 2 1 ln( x ) x dx = Z ln(2) 0 udu = 1 ln(2) ± 1 2 u 2 ² ln(2) 0 = ln(2) 2 b) Letting u = 3 - e x we have du = - e x dx , x = 0 u = 2, x = ln(2) u = 1. Therefore Z ln(2) 0 e x (3 - e x ) 2 dx = Z 1 2 - du u 2 = ± 1 u ² 1 2 = 1 1 - 1 2 = 1 2 c) Letting u = e 2 x we have e 4 x = u 2 and du = 2 e 2 x dx . So Z e 2 x 1 + e 4 x dx = 1 2 Z du 1 + u 2 = 1 2 tan - 1 ( u ) + C = 1 2 tan - 1 ( e 2 x ) + C d) Use integration by parts. Z ln 2 ( x ) dx = Z 1 · ln 2 ( x ) dx = x ln 2 ( x ) - Z x · 2 ln( x ) 1 x dx = x ln 2 ( x ) - 2 Z ln( x ) dx = x ln 2 ( x ) - 2 Z 1 · ln( x ) dx = x ln 2 ( x ) - 2( x ln( x ) - Z x · 1 x dx ) = x ln 2 ( x ) - 2 x ln( x ) + 2 Z dx = x ln 2 ( x ) - 2 x ln( x ) + 2 x + C e) Write x +1 x 3 + x = A x + Bx + C x 2 +1 . Then x + 1 = A ( x 2 + 1) + ( Bx + C ) x = ( A + B ) x 2 + Cx + A . This shows that

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 2

prelim2_fa09solutions - Math 1910 Prelim 2 Solutions 1 a...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online